Assessment of Using 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in Patients with Carcinoma of Unknown Primary - S. A. Yaremenko; N. A. Ruchyeva; V. E. Sinitsyn (Вестник рентгенологии и радиологии)
Objectives: to assess the possibility of using 18F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) in patients with carcinoma of unknown primary (CUP); to determine the effectiveness of PET/CT for detecting a primary tumor lesion in patients with a histologically verified diagnosis of CUP and the contribution of PET/CT procedure to the process of disease staging in these patients.Material and methods. From September 2018 to March 2019, the retrospective study included a total of 187 patients (64 (34.2%) females and 123 (65.8%) males) diagnosed with CUP. The patients’ mean age was 61.9 ± 7.5 years. Before PET/CT, all the patients underwent puncture biopsy of at least one metastatic lesion, which histologically verified the malignant nature of the neoplasm. A number of conventional studies were also performed as part of an oncosearch to identify the nature of a primary cancer lesion.Results. Biopsy of lymph node metastases in 187 patients included in the study showed the following distribution according to the histological types of the tumor: 87 (46.5%) patients were diagnosed with squamous cell carcinoma, 15 (8%) with melanoma, 45 (24.1%) with undifferentiated carcinoma, 23 (12.3%) with adenocarcinoma, 17 (9.1%) with undifferentiated malignant neoplasm. The examination could identify a primary tumor site in 93 (49.7%) patients; no primary source was found in 94 (50.3%) patients. After PET/CT, there were no significant differences in the age of patients with and without CUP. PET/CT revealed new, previously undetected metastatic lesions in 93 cases, accounting for 49.7% of the entire sample. It is worth noting that after PET/CT, a change in the stage of tumor development tool place in 131 (70.1%) cases, which was associated with both the detection of the primary tumor and the identification of new metastatic lesions. The stage change was significantly more frequently observed in patients with detected CUP than in those with undetected CUP (100% vs. 40.4%; p < 0.001).Conclusion. PET/CT can more accurately determine the stage of cancer in a large proportion of patients with CUP. The technique is able to identify the primary tumor in a significant number of cases, which in turn affects treatment policy and prognosis in these patients. The use of PET/CT should be obligatorily included in the examination protocol for patients with CUP.